2021
DOI: 10.1002/2211-5463.13128
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide B promotes proliferation and differentiation of rat brown primary preadipocytes

Abstract: Neuropeptide B (NPB) is reported to regulate energy homeostasis and metabolism via the NPBWR1 and NPBWR2 receptors in various tissues. However, the molecular mechanisms triggered from their interaction are not well investigated in brown adipose tissue. In this study, we specifically analyzed the role of NPB in controlling brown adipogenesis in rat brown preadipocytes. We first detected the expression of NPBWR1 and NPB on mRNA and protein level in brown preadipocytes and observed that NPB increased viability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recently, we found that NPB is able to promote ERK1/2 phosphorylation in insulin-producing INS-1E cells [ 10 ]. Furthermore, we reported that NPB induces the phosphorylation of p38 kinase in rat white and brown primary preadipocytes [ 14 , 27 ]. As indicated in the introduction, both protein kinases, p-38 and ERK1/2, are involved in controlling adipogenesis [ 42 , 43 , 44 ], so we therefore studied whether NPB is able to modulate the phosphorylation of these protein kinases in porcine preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that NPB is able to promote ERK1/2 phosphorylation in insulin-producing INS-1E cells [ 10 ]. Furthermore, we reported that NPB induces the phosphorylation of p38 kinase in rat white and brown primary preadipocytes [ 14 , 27 ]. As indicated in the introduction, both protein kinases, p-38 and ERK1/2, are involved in controlling adipogenesis [ 42 , 43 , 44 ], so we therefore studied whether NPB is able to modulate the phosphorylation of these protein kinases in porcine preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we provided evidence that NPB may be involved in controlling white and brown adipogenesis. Using rodent primary preadipocytes as well as the murine 3T3-L1 cell line, we found that NBP stimulates the proliferation and differentiation of brown and white preadipocytes [ 14 ]. These data suggest that NPB may be involved in controlling fat tissue formation in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the function of modulating white adipocytes, our recent data indicate that NPB may be involved in brown adipogenesis [ 28 ]. We demonstrated that NPB promotes proliferation of rat primary preadipocytes.…”
Section: The Role Of Npb In Regulating Glucose and Lipid Metabolismmentioning
confidence: 99%